Natriuretic Peptide and Transthyretin and Their Relationship With Clinical Outcomes: Results From ATTRIBUTE‐CM, a Randomized Controlled Trial - Onyedika John Ilonze; Daniel Philip Judge; Ahmad Masri; Prem Soman; Francesco Cappelli; Michel Georges Khouri; Nitasha Sarswat; Mazen Hanna; Yuxi Liu; Gillian Murtagh; Kuangnan Xiong; Adam Castaño; et al. (Journal of the American Heart Association, 2026)
Background Transthyretin amyloid cardiomyopathy (ATTR‐CM) carries high risk for all‐cause mortality (ACM), cardiovascular mortality (CVM), and cardiovascular hospitalization (CVH). NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) and serum TTR (sTTR) are prognostic biomarkers in transthyretin amyloid cardiomyopathy, but their combined value for integrated risk stratification remains unknown. We evaluated the relationship between baseline NT‐proBNP and sTTR and their prognostic value in ATTRIBUTE‐CM (Efficacy and Safety of Acoramidis in Transthyretin Amyloid Cardiomyopathy). Methods ATTRIBUTE‐CM was a phase 3, randomized, double‐blind, placebo‐controlled trial. Among 632 participants randomized to acoramidis or placebo, baseline NT‐proBNP and sTTR concentrations were evaluated post hoc for associations with baseline characteristics, Kansas City Cardiomyopathy Questionnaire overall scores, 6‐minute walk distance, National Amyloidosis Center stage, Geriatric Nutritional Risk Index score, and subsequent time to ACM/first CVH and CVM/first CVH through Month 30. Results Higher baseline NT‐proBNP and lower sTTR were associated with greater disease severity and were inversely correlated. Using multivariable linear regression, sTTR remained inversely correlated with NT‐proBNP. Using multivariable Cox analyses, baseline NT‐proBNP and sTTR were each independently associated with ACM/first CVH and CVM/first CVH. Higher baseline NT‐proBNP combined with lower sTTR conferred higher risk and shorter time to event. Acoramidis reduced risk of ACM/first CVH and CVM/first CVH regardless of baseline NT‐proBNP/sTTR, National Amyloidosis Center stage, or Geriatric Nutritional Risk Index. Conclusions Baseline NT‐proBNP and sTTR were additively prognostic for ACM/first CVH and CVM/first CVH in patients with transthyretin amyloid cardiomyopathy. Their joint measurement may be useful for enhanced staging, risk stratification, and prognostication in transthyretin amyloid cardiomyopathy. Acoramidis demonstrated consistent clinical efficacy regardless of baseline NT‐proBNP/sTTR status. Registration URL: https://clinicaltrials.gov/study/NCT03860935 ; Unique Identifier: NCT03860935. Registered: February 2019.